Anti-inflammatory effect of 3-acetylaconitine - TANG Xi-can; LIN Zhi-gong; CAI Wen; CHEN Nian; SHEN Li (Acta Pharmacologica Sinica, 2016)
3-Acetylaconitine (AAc), isolated from Aconitum flavum,0.18-0.3 mg/kg ig inhibited considerably the increased vascular permeability induced bu ip 0.7% Hac in mice or histamine ic 0.05 μg/0.05 ml in rats. AAc 0.3-0.5 mg/kg inhibited the swelling of hind paw induced by injection of 2.5% formaldehyde 0.1 ml and on the cotton-pellet granuloma in rats daily medication for 6 d. AAc inhibited markedly the edema produced by injection of 1% carrageenin 0.1 ml or fresh egg white 0.1 ml beneath the plantar surface of hind paw in intact or in adrenalectomized rats. AAc neither reduced the content of ascorbic acid of adenal in intact rats nor prolonged the surviving time in adrenalectomized rats. AAc was effective in the granuloma inhibition test when AAc was added directly to the cotton pellet. These results indicate that AAc action does not depend on stimulatation of the pituitaryadrenal axis. AAc 40 μg/kg ip significantly reduced the fever induced by sc 7% yeast suspension 3 ml/kg in rats.